Breastfeeding With Infectious Diseases - Samantha Yeo; Liying Yang; Kirsten Ong; Tze Tein Yong (Proceedings of Singapore Healthcare, 2022)
Aims: Human breast milk remains an important source of protection against infection, inflammation, allergy and long-term metabolic disorders for the breastfed offspring. During cases of ongoing infection, the dilemma faced by both medical health professionals and mothers is the need to balance the risk of continuing versus temporarily or permanently ceasing to breastfeed. The aim of our article is to review existing literature regarding breastfeeding during acute infectious and non-infectious illnesses and to provide feasible evidence-based suggestions which can be implemented by medical practitioners during counselling of breastfeeding mothers. Method: A literature search was conducted on PubMed (US National Library of Medicine) using various combinations of keywords related to breastfeeding and the various infections. The citations from all selected articles were reviewed for additional studies. Results: Most ongoing infections are not contraindications for breastfeeding, with the exceptions of Human Immunodeficiency viruses (HIV), Human T-cell lymphotropic virus (HTLV) types 1 and 2. Even with HIV, there is increasing evidence to reassure that with adequate antiretroviral therapy, breastfeeding is likely to be safe. Of particular concern during the COVID-19 pandemic too, current evidence indicates that mothers with COVID-19 infection can safely breastfeed, and therefore initiation and continuation of breastfeeding should continue to protect the health of the babies and mothers. Conclusion: During this pandemic especially, there is a strong and urgent need to support mothers with acute infections who wish to breastfeed. With better awareness, physicians can play an important role in securing positive experiences for breastfeeding mothers and optimizing infant outcomes.